2021
DOI: 10.2147/cmar.s298165
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Value of Detecting Tumor Endothelial Marker 8 (ANTXR1) as a Biomarker in the Diagnosis and Prognosis of Colorectal Cancer

Abstract: Background Despite the continuous improvements in prevention and detection of colorectal cancer (CRC), there is an urgent need to find a sensitive, specific, and noninvasive biomarker to improve the early diagnosis and prognosis of CRC. We aimed to evaluate the tissue TEM8 expression and the serum TEM8 concentration in CRC patients. Methods The study enrolled 42 CRC patients and 35 controls. Immunohistochemical staining was performed to assess the TEM8 tissue expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Thus, detection of serum ANTXR1 may serve as a diagnostic biomarker and clinical predictor of CRC. 17 Meanwhile, high ANTXR1 expression was strongly correlated with stromal and immune infiltration in gastric cancer. 18 APOC1, APOC2, APOC3, Orm1, and Orm2 are associated with lipoprotein metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, detection of serum ANTXR1 may serve as a diagnostic biomarker and clinical predictor of CRC. 17 Meanwhile, high ANTXR1 expression was strongly correlated with stromal and immune infiltration in gastric cancer. 18 APOC1, APOC2, APOC3, Orm1, and Orm2 are associated with lipoprotein metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Another novel target for ADC development has been TEM8, a transmembrane glycoprotein initially found to be a TEM but more recently also shown to be expressed widely in the tumour stroma across several human tumours [121][122][123]. The TEM8 targeting m825 [124] was developed into an ADC by conjugating it with MMAE via a cleavable linker.…”
Section: The Tme-a Promising Area For Adc Developmentmentioning
confidence: 99%
“…Studies have demonstrated that TEM8/ANTXR1 is enriched in triple negative breast cancer (Xu et al, 2021), prostate cancer (Li et al, 2021a), gastric cancer (Li et al, 2021b;Sun et al, 2021), pancreatic cancer (Alcalá et al, 2019), angiosarcoma (Kusaba et al, 2021(Kusaba et al, ), colon cancer (Ł et al, 2021, and non-small cell lung cancer (NSCLC) (Gong et al, 2021). In multiple tumor types, upregulation of TEM8/ ANTXR1 is a negative prognostic indicator (Li et al, 2021a;Ł et al, 2021;Ding et al, 2021). In triple negative breast cancer, TEM8/ANTXR1, is marker of vasculogenic mimicry, and is associated with poor outcomes (Fernández-Cortés et al, 2019;Xu et al, 2021).…”
Section: Study Description Outcomesmentioning
confidence: 99%